2008
DOI: 10.1364/ol.33.001395
|View full text |Cite
|
Sign up to set email alerts
|

Multiple fiber Bragg grating interrogation based on a spectrum-limited Fourier domain mode-locking fiber laser

Abstract: A novel fiber Bragg grating (FBG) sensing system based on a spectrum-limited Fourier domain mode-locking (SL-FDML) fiber laser is proposed. Multiple FBGs cascaded in a long fiber are utilized as both the sensors in the system and the wavelength-selected components in the SL-FDML fiber laser. Both wavelength-division multiplexing and spatial-division multiplexing techniques are demonstrated for interrogation of multiple FBGs by mapping the wavelength measurement to the time measurement and by adjusting the driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 8 publications
0
33
0
Order By: Relevance
“…Hu et al in reference [63] also showed a 150 km long distance FBG sensor system combining Raman and EDF amplification. The FBG 150 km far away from the monitoring station only offered 1 dB of OSNR.…”
Section: Demonstrated Systemsmentioning
confidence: 99%
“…Hu et al in reference [63] also showed a 150 km long distance FBG sensor system combining Raman and EDF amplification. The FBG 150 km far away from the monitoring station only offered 1 dB of OSNR.…”
Section: Demonstrated Systemsmentioning
confidence: 99%
“…Nowadays, the main disadvantage of this type of technology resides on the considerable cost of the interrogation system. Nevertheless several techniques have been investigated to make this type of sensors cost effective [11,[16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Optical fiber sensors [1][2][3][4][5][6][7][8][9][10][11][12][13] have attracted considerable attention in the past several decades due to their wide applications for a great variety of measurements such as temperature, strain, chemical concentration, refractive index, hydrostatic pressure and their advantages such as small size, light weight, high sensitivity, multiplexing capability, and immunity to electromagnetic interference. Among them, several hydrostatic pressure sensing techniques have been developed, which include hydrostatic pressure sensors based on birefringent fibers [14][15][16], photonic crystal fibers (PCFs) (or microstructured fibers) [17][18][19][20][21][22][23][24], fiber Bragg gratings (FBGs) [18], and Fabry-Pérot interferometers (FPIs) [25][26][27].…”
Section: Introductionmentioning
confidence: 99%